Profiles of Clinical and Liver Function Test of Hepatitis B and C Patients with Liver Cirrhosis - Andreas Novaldi Watang; Aryati Aryati; Ulfa Kholili (Universitas Airlangga, 2023)
Highlights:1. Liver cirrhosis due to viral hepatitis is still a big problem in developing countries.2. There were no significant differences in clinical and laboratory profile results between patients with liver cirrhosis caused by hepatitis B and C. AbstractIntroduction: Liver cirrhosis is a degenerative liver disease that ranks 14th as a global problem and has a high prevalence rate. This study aimed to determine the clinical and laboratory profile of inpatients with liver cirrhosis.Methods: Medical record data of liver cirrhosis patients at Dr. Soetomo General Academic Hospital, Surabaya, in 2018-2019, were used in this cross-sectional descriptive observational study. The results were analyzed statistically to determine the different profiles between patients with liver cirrhosis caused by hepatitis B and C.Results: 112 subjects in this study had liver cirrhosis caused by hepatitis B or C. The majority of cirrhotic patients were males over 40 years old. Melena was the most frequent complaint, and abdominal enlargement and hepatitis B virus (HBV) infection were the most common causes. Liver function tests in hepatitis B and C patients respectively showed albumin results of 2.73 g/dL (± 0.54); 2.75 g/dL (± 0.61), prothrombin time was 14.75 seconds (10.80-49.40); 14.9 seconds (11.1-19.1), direct bilirubin 1.17 mg/dL (0.9-17.05); 0.82 mg/dL (0.12-8.43), total bilirubin 2.18 mg/dL (0.28-24.9); 1.58 mg/dL (0.38-9.7), AST 50.5 U/L (16-826); 48.5 U/L (31-545), ALT 51.5 U/L (8-869); 38.5 (12-127). Subjects with hepatitis B and C had a median length of stay of 7.00 days, with an overall mean of 7.16 days. There was no significant difference in the results between patients with liver cirrhosis due to hepatitis B and C.Conclusion: There was no significant difference between patients with liver cirrhosis caused by hepatitis B and C.